Penyusunan Indeks Pembangunan Smart City Di Indonesia Tahun 2018 - Nabil Miftah Irfandha; Jeffry Raja Hamonangan Sitorus (Politeknik Statistika STIS, 2021)
Development in urban areas requires city management to solve problems that occur as a result of high population growth. The complexity of problems in urban areas varies greatly, including a decrease in the quality of public services, reduced availability of residential land, congestion on the highway, excessive energy consumption, garbage accumulation, increased crime rates, and other social problems. The establishment of the Smart City Development Index (SCDI) is seen as being able to provide effective and efficient solutions in reducing existing urban problems. The purpose of this study is to determine the general picture and obtain the factors forming SCDI, get SCDI measurement results, study the uncertainty analysis and sensitivity analysis of SCDI and see the relationship between SCDI and HDI, and get a classification based on 5 categories in Indonesia. Based on the results of the factor analysis, there were 6 factors formed where the highest SCDI area with a population of less than 200,000 people is in Madiun City, the highest IPSC area with a population between 200,000 to 1,000,000 people is in Yogyakarta City and the highest IPSC area with a population above 1,000,000 people is in Tangerang City. The results of uncertainty analysis and sensitivity analysis showed that the SCDI that was formed was quite robust and reliable. In generally SCDI had a positive relationship with HDI. The establishment of this index is expected to be able to facilitate local and central government in reviewing policies regarding the allocation of funds so that the expected development of smart city is in accordance with existing conditions.